2021
DOI: 10.1002/dev.22199
|View full text |Cite
|
Sign up to set email alerts
|

Medial prefrontal brain activity correlates with emerging symptoms of anxiety and depression in late adolescence: A fNIRS study

Abstract: The brain undergoes dramatic changes over the course of the adolescent years, and these developmental changes are implicated in the emergence of disorders that involve negative emotionality. Late adolescence might be the window within which brain networks manifest vulnerabilities to depressive and anxiety symptomology; particularly within the prefrontal cortex (PFC), which houses emotional control (dorsolateral) and emotional processing (medial) nodes. Given the comorbidity of depressive and anxious symptomolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Thus, these findings suggested that a performance improvement in cognitive capacity accompanied with SFBT therapy. The neural signatures of anxiety and depressive symptoms within the prefrontal cortex (PFC) were found to be similar when using fNIRS, had less cortex activation during the tasks compared to healthy controls (HCs) particularly in the medial subregions, indicating a potential shared neural basis for these symptoms during late adolescence (32,33). Zhang et al found that MDD patients had considerably decreased PFC activation and were associated with reduced rise in oxy-Hb in prefrontal regions when undertaking cognitive tasks relative to controls (34).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these findings suggested that a performance improvement in cognitive capacity accompanied with SFBT therapy. The neural signatures of anxiety and depressive symptoms within the prefrontal cortex (PFC) were found to be similar when using fNIRS, had less cortex activation during the tasks compared to healthy controls (HCs) particularly in the medial subregions, indicating a potential shared neural basis for these symptoms during late adolescence (32,33). Zhang et al found that MDD patients had considerably decreased PFC activation and were associated with reduced rise in oxy-Hb in prefrontal regions when undertaking cognitive tasks relative to controls (34).…”
Section: Discussionmentioning
confidence: 99%
“…In the current systematic review, developmental increase in prefrontal hemodynamic activity was reported in three domains of executive functioning, including inhibition control ( 23 , 84 , 86 , 87 , 89 ), working memory ( 90 , 91 ), and mental flexibility in typically developing children ( Figure 4 ) ( 26 , 27 , 95 ). This finding from studies using fNIRS is consistent with studies using EEG and fMRI ( 118 , 119 ).…”
Section: Discussionmentioning
confidence: 85%
“…TD children were found to have age-related increases in prefrontal activation in response to Flankers, Stroop, and go/no-go tasks, from childhood to adulthood ( 23 , 84 , 86 , 87 ). Similarly, Papasideri et al reported that age was a significant moderator of the relationship between bilateral medial PFC and general anxiety disorder, and the neural activity over this brain region predicted the anxiety, depression, and negative affect more strongly in older adolescents than in the younger ones ( 89 ). However, age-related differences were less consistent in children with obesity and ADHD ( 23 , 24 , 85 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the extent of this problem appears to be negligible in recent fNIRS systems and may be mitigated with the inclusion of short channels. 92,93 Finally, while some laser-and LED-based fNIRS systems are silent, others generate noticeable levels of noise that could be distracting or serve as confound in auditory experiments. The noise level tends to correlate with the size of the system; so, wearable/portable systems are more likely to be silent while fiber-based systems are likely to generate more low-level noise from the cooling fans and other components inside the amplifier box.…”
Section: Introduction To Functional Near-infrared Spectroscopymentioning
confidence: 99%
“…However, the extent of this problem appears to be negligible in recent fNIRS systems and may be mitigated with the inclusion of short channels. 92 93…”
Section: Introduction To Functional Near-infrared Spectroscopymentioning
confidence: 99%